The Role of Notaries in Murabahah Financing Agreements - Ginting, Lilawati (Lembaga Riset Mutiara Akbar, 2024)
The role of notaries in the legal system in Indonesia is very significant, especially in supporting legal certainty in the Islamic banking sector through the Murabahah financing contract. This contract is based on the principle of buying and selling with agreed profits, so it requires a notary to prepare documents that comply with positive law and sharia principles. Notaries are authorized to make authentic deeds, provide legal counseling, and ensure the validity of each element of the agreement, including payment clauses, profits, and fines. In this case, notaries act as legal guardians who guarantee transparency and justice, prevent potential violations of law such as usury practices, and reduce the risk of future disputes. This study uses a normative legal approach by examining related legislation, such as Law No. 2 of 2014 concerning the Position of Notaries and Islamic Banking Law. The study results show that notaries have a dual role: as legal enforcers who ensure that documents meet legal requirements and as law enforcers who maintain the integrity of the transaction process. With the increasing need for Sharia financing, the existence of notaries is becoming increasingly relevant to support equitable Sharia-based economic development. In conclusion, notaries are a key element in Murabahah transactions that not only function administratively but also substantively, helping to create a transparent and trusted financial system in Indonesia. This strengthens the position of notaries as an important pillar in ensuring the sustainability of Sharia-based law and economy.